Sistem Peradilan Pidana Progresif; Alternatif dalam Penegakan Hukum Pidana - Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2007)
There will be some implications if progressive law idea is applied on the criminal law judiciary system to enforce the law. The implications are firstly, the police will not use the written law as primary instrument in combating crimes, but they are going to place forward the conscience, secondly, unloading coherent characteristic at public attorney, that is bureaucratic sentralistic, and go into effect the comando system embracing responsibility hierachie, and thirdly, the court ( judge ) should not handle the case only based on written law but also placed forward on conscience, because the law is created for the citizen and not inversed. The task of the judges are not only as technical Acts but they are also as a social creature.